The enterprise as the experiential design platform - Baskerville, Richard (Springer-Verlag, 2013)
Individuals are autonomously designing, creating, and operating their own complex, idiosyncratic information systems. These systems are designed in an experiential and emergent way. This growing individual technological autonomy creates dynamic bindpoints where formerly there were relatively static user endpoint interfaces across an air gap. This enables the organization to adjust the location of its enterprise system bindpoints in relation to the individual system endpoints. © 2013 Springer-Verlag.